Gene expression profiling and real-time PCR analyses identify novel potential cancer-testis antigens in multiple myeloma - Condomines, Maud; Hose, Dirk; Rème, Thierry; Requirand, Guilhem; Hundemer, Michael; Schoenhals, Matthieu; Goldschmidt, Hartmut; Klein, Bernard (The journal of immunology, 2009)
Cancer-testis (CT) Ags are attractive targets for immunotherapeutic strategies since they are aberrantly expressed in malignant cells and not, or in limited number, in somatic tissues, except germ cells. To identify novel CT genes in multiple myeloma, we used Affymetrix HG-U133 gene expression profiles of 5 testis, 64 primary multiple myeloma cells (MMC), and 24 normal tissue samples. A 5-filter method was developed to keep known CT genes while deleting non-CT genes. Starting from 44,928 probe sets, including probe sets for 18 previously described CT genes, we have obtained 82 genes expressed in MMC and testis and not detected in more than 6 normal tissue samples. This list includes 14 of the 18 known CT genes and 68 novel putative CT genes. Real-time RT-PCR was performed for 34 genes in 12 normal tissue samples, 5 MMC samples, and one sample of five pooled testes. It has validated the CT status of 23 of 34 genes (67%). We found one novel “testis-restricted” gene (TEX14, expression in testis and tumor only), eight “tissue-restricted” (mRNA detected in one or two nongametogenic tissues), and seven “differentially expressed” (mRNA detected in three to six nongametogenic tissues) CT genes. Further studies are warranted to determine the immunogenicity of these novel CT Ag candidates.
Gesehen am 14.01.2022